Relations among Earnings Quality, Information Asymmetry and Cost of Equity - Ghasem Blue (Shahid Bahonar University of Kerman, 2014)
Investors and creditors use income and its components to evaluate cash flows, investments and granted loans in different ways and for different purposes. This study uses panel data analysis to examine the relations among earnings quality, information asymmetry and costs of equity holders. The study sample consists of 72 companies listed in the Tehran Stock Exchange in the period of 1387 to 1391. The independent variables that affect cost of equity risk management and information asymmetry, take market risk, firm size, the ratio of book value to market value, the stock price and trading volume. Also, earnings quality for firm/year data have been measured, using accounting data in a 5 year period and rolling linear regression. Hypothesis test results indicated a significant positive relationship between information asymmetry and cost of equity, and a significant negative relationship between information asymmetry and earnings quality. The results also showed a non-significant relationship between earnings quality and the cost of equity.